(untitled) (INNOVATIVE ECONOMY, 2022)
Holei Yu.M., Stasiuk Yu.M., Krupskyi O.P. RESEARCH ON WORLD TRENDS IN BIOTECHNOLOGY DEVELOPMENT Purpose. The aim of the article is to study the practice and peculiarities of organization and development of biotechnology industries in the world, to identify common features of the economy of the industry enterprises, to determine the main trends of the world biotechnology market. Methodology of research. Theoretical and methodological principles of the article are based on the fundamental provisions of modern economic science. The following methods were used in the process of the research: theoretical generalization and scientific abstraction - when studying the basic concepts and categories of the study; method of system analysis - when forming the methodological base of the study; method of comparative analysis - when identifying regional and temporal patterns of development of biotechnology; tabular and graphical - for visual representation of the dynamics and structure of the analyzed indicators; generalization - to substantiate the conclusions. Findings. The features of economics and organization of biotechnology industries are considered, with an emphasis on the most exemplary international experience. The biotechnology is considered as a branch including many specific enterprises which have common features in the organization of the production and management process. Specific and common characteristics of biotechnology industries are highlighted with respect to the organization of management, the technologies used in management, attracting investment and the implementation of the whole range of business processes. Originality. Studies of the trends in the development of biotechnologies worldwide have been further developed. Future research will focus on the potential for biotechnology development in Ukraine. Practical value. Determination of global trends in biotechnology production can serve as prerequisites for the development of biotechnology in Ukraine. Key words: scientific and technological progress, biotechnology, biotechnology production, biotechnology companies, the world market for biotechnology.